(untitled) (Práxis Educativa, 2025)
Academic misconduct, defined as any intentional behavior that violates the ethical principles of educational institutions, is a phenomenon that deserves special attention in the field of postgraduate studies. Its study is essential to understand the fraudulent practices committed by students, the factors that motivate them, and the measures implemented to combat them. This article aims to analyze the current state of research on academic dishonesty among postgraduate students. Specifically, it seeks to identify the most common illicit practices reported by different informants (students, faculty, and academic heads), analyze the factors driving these behaviors, and describe the measures universities adopt to address this issue. To this end, a systematic and critical review of the literature was conducted, following the guidelines of the PRISMA model. By consulting four databases (Web of Science, Scopus, Dialnet, and Eric), 594 articles published between 2020 and 2024 were identified, of which, according to the criterion of including only those studies whose analysis was carried out exclusively with postgraduate populations, 27 were selected for analysis. From these, it is concluded that the most frequent practices are plagiarism, inappropriate authorship, and data manipulation. Among the main driving factors are the pressure to publish, academic isolation, lack of ethical training, and power hierarchies. Although punitive measures predominate, preventive strategies focused on awareness-raising, training, and faculty support are beginning to take shape. The review highlights the need to articulate policies that combine regulatory frameworks, prevention, and a shared ethical culture to ensure the quality and sustainability of postgraduate education. Keywords: Academic misconduct. Academic integrity. Postgraduate studies. Higher education. Systematic review.